Three-Dimensional Compaction Switches Stress Response Programs and Enhances Therapeutic Efficacy of Endometrial Mesenchymal Stem/Stromal Cells - Domnina, Alisa; Ivanova, Julia; Alekseenko, Larisa; Kozhukharova, Irina; Borodkina, Aleksandra; Pugovkina, Natalia; Smirnova, Irina; Lyublinskaya, Olga; Fridlyanskaya, Irina; Nikolsky, Nikolay (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stem cells are currently tested as a promising tool for the treatment of a wide range of human diseases. Enhanced therapeutic potential of spheroids formed from these cells has been proved in numerous studies, however, the fundamental basics of this effect are still being discussed. In this work, we showed that endometrial mesenchymal stem/stromal cells (eMSCs) assembled in spheroids possess a higher therapeutic efficacy compared to monolayer grown cells in the treatment of the defects that are non-specific for eMSC tissue origin – skin wounds. With the purpose to elucidate the possible reasons of spheroid superior potency, we compared the tolerance of eMSC cultivated in spheres and monolayer to the stress insults. Using genetically encoded hydrogen peroxide biosensor HyPer, we showed that three-dimensional configuration (3D) helped to shield the inner cell layers of spheroid from the external H2O2-induced oxidative stress. However, the viability of oxidatively damaged eMSCs in spheroids appeared to be much lower than that of monolayer cells. An extensive analysis, which included administration of heat shock and irradiation stress, revealed that cells in spheroids damaged by stress factors activate the apoptosis program, while in monolayer cells, a stress-induced premature senescence is developed. We found that basal down-regulation of anti-apoptotic and autophagy-related genes provides the possible molecular basis of the high commitment of eMSCs cultured in 3D to apoptosis. We conclude that predisposition to apoptosis provides the programmed elimination of damaged cells and contributes to the transplant safety of spheroids. In addition, to investigate the role of paracrine secretion in the wound healing potency of spheroids, we exploited in vitro wound model (scratch assay) and found that culture medium conditioned by eMSC spheroids accelerates the migration of adherent cells. We showed that 3D eMSCs upregulate transcriptional activator, hypoxia inducible factor HIF1, and secret ten-fold more HIF1-inducible pro-angiogenic factor VEGF (vascular endothelial growth factor) then monolayer cells. Taken together, these findings indicate that enhanced secretory activity can promote wound healing potential of eMSC spheroids and that cultivation in 3D cell environment alters eMSC vital programs and therapeutic efficacy.